SMARTDSM: data space middleware for distributed measurement systems = SMARTDSM: platforma middleware do agregacji danych dla rozproszonych systemów pomiarowych - Koropiecki, Igor; Piotrowski, Krzysztof; Szulim, Robert (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article describes a platform that consists of multiple module witch together allow accelerate the process of setting up a secure communication and data storage solution. The implementation approach make sit possible to apply the platform in many deployments that can be interconnected on the data and communication layers.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne